2020
DOI: 10.1002/mp.13988
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a synthetic diamond detector response in kilovoltage photon beams

Abstract: Purpose An important characteristic of radiation dosimetry detectors is their energy response which consists of absorbed‐dose and intrinsic energy responses. The former can be characterized using Monte Carlo (MC) simulations, whereas the latter (i.e., detector signal per absorbed dose to detector) is extracted from experimental data. Such a characterization is especially relevant when detectors are used in nonrelative measurements at a beam quality that differs from the calibration beam quality. Having in mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Its impact would be higher where the signal is comparatively smaller, which in our case would be at larger distances and smaller angles. (c) Angular dependence of the factor k bq : Kaveckyte et al 45 have shown that mDDs have a non‐negligible variation of the relative intrinsic energy dependence for effective photon energies <140 keV, which can lead to an over‐response by a factor 2. Although the effective photon energies in our investigated range are considerably higher than 140 keV, it is possible that low energy components of the spectrum, which are expected to have a comparatively larger impact at (3 cm, 0°) and (5 cm, 0°), could cause an over‐response of the mDD, so that the approximation of treating k bq as a constant in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Its impact would be higher where the signal is comparatively smaller, which in our case would be at larger distances and smaller angles. (c) Angular dependence of the factor k bq : Kaveckyte et al 45 have shown that mDDs have a non‐negligible variation of the relative intrinsic energy dependence for effective photon energies <140 keV, which can lead to an over‐response by a factor 2. Although the effective photon energies in our investigated range are considerably higher than 140 keV, it is possible that low energy components of the spectrum, which are expected to have a comparatively larger impact at (3 cm, 0°) and (5 cm, 0°), could cause an over‐response of the mDD, so that the approximation of treating k bq as a constant in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that non-intrinsic beam quality dependence was accounted for in the calculations. Our study did not take into account the intrinsic beam quality dependence of the response, which was shown to increase substantially with reducing effective photon energy from 375 keV to below 13 keV (Kaveckyte et al 2020). Below 50 keV, however, the response variation shows more variability depending on the assumed sensitive volume thickness.…”
Section: Validation Of the MC Modelmentioning
confidence: 92%
“…On the other hand, the intrinsic energy dependence R Q 0 ,Q is determined by combining MC and measurements. [33][34][35] It is thus clear that the accuracy of the determined absorbed dose to water relies on complete characterization of detector response using both MC and experimental methods, and on the knowledge under what measurement conditions the detector response changes regardless of the magnitude of the change itself.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The quantity fQ,Q0$f_{Q,Q_{0}}$ is referred to as a ratio of the absorbed‐dose energy dependence of detector cavity relative to water in beam qualities Q and Q 0 , and can be calculated using MC methods alone. On the other hand, the intrinsic energy dependence RQ0,Q$R_{Q_{0},Q}$ is determined by combining MC and measurements 33–35 . It is thus clear that the accuracy of the determined absorbed dose to water relies on complete characterization of detector response using both MC and experimental methods, and on the knowledge under what measurement conditions the detector response changes regardless of the magnitude of the change itself.…”
Section: Theoretical Backgroundmentioning
confidence: 99%